2017
DOI: 10.1016/j.joca.2017.02.381
|View full text |Cite
|
Sign up to set email alerts
|

The Illness Burden of Knee Osteoarthritis in China: A Prospective Study

Abstract: curve (ROC) methods to minimize misclassification bias. As the positive predictive value (PPV) increased when II was calculated by tertile (T) of baseline severity, we report those results. Results: Sample mean age was 65.1 years (range 43e90) and 55% were female. 80% reported at least one comorbid condition. For pain, T1 (mean 26.0, range 0e35) the II was 45; T2 (mean 48.7, range 40e55) the II was 30; and, T3 (mean 71.1, range 60e100) the II was 25. The overall PPV was 0.92. For function, T1 (mean 29.1, range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…With the growing aging population in China, the incidence of osteoarthritis is predicted to significantly increase in the near future . Osteoarthritis now has become a heavy burden on public health in China . The pathogenesis of osteoarthritis is a complex network composed of interactions between anabolic, catabolic, and inflammatory signals, while the genetic factors involved are poorly characterized .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing aging population in China, the incidence of osteoarthritis is predicted to significantly increase in the near future . Osteoarthritis now has become a heavy burden on public health in China . The pathogenesis of osteoarthritis is a complex network composed of interactions between anabolic, catabolic, and inflammatory signals, while the genetic factors involved are poorly characterized .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Osteoarthritis now has become a heavy burden on public health in China. 4 The pathogenesis of osteoarthritis is a complex network composed of interactions between anabolic, catabolic, and inflammatory signals, while the genetic factors involved are poorly characterized. 5 A deeper understanding of the molecular pathogenesis of osteoarthritis is required for the treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…With an aging population and obesity epidemic, the incidence of KOA has been increasing year by year ( 4 ). A survey in 2018 found that the overall incidence rate of KOA in China was 18%, 11% in men, and 19% in women ( 5 ). American College of Rheumatology (ACR) launched a pyramid scheme of KOA treatment, which was based on measures of education, exercise, and weight reduction, supplementing externally used non-steroidal anti-inflammatory drugs (NSAIDs) if necessary, adding the use of acetaminophen and NSAIDs orally under the ineffective situation, and performing intra-articular corticosteroid injections during acute attack ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, knee osteoarthritis (OA) is a common chronic osteoarticular disease characterized by articular cartilage degeneration and joint pain, and the main manifestations of OA include stiffness and pain at the affected part as well as limited mobility [ 6] . The OA disease population is concentrated in women over 65 years old, and it has become one of the major disability diseases among the elderly in China [ 7] . A variety of mechanisms are involved in the pathogenesis of OA, including increased proteases and release of tumour necrosis factor.…”
Section: Introductionmentioning
confidence: 99%